2010
DOI: 10.1099/mic.0.036509-0
|View full text |Cite
|
Sign up to set email alerts
|

LAP, an alcohol acetaldehyde dehydrogenase enzyme in Listeria, promotes bacterial adhesion to enterocyte-like Caco-2 cells only in pathogenic species

Abstract: Listeria adhesion protein (LAP), an alcohol acetaldehyde dehydrogenase (lmo1634), interacts with host-cell receptor Hsp60 to promote bacterial adhesion during the intestinal phase of Listeria monocytogenes infection. The LAP homologue is present in pathogens (L. monocytogenes, L. ivanovii) and non-pathogens (L. innocua, L. welshimeri, L. seeligeri); however, its role in nonpathogens is unknown. Sequence analysis revealed 98 % amino acid similarity in LAP from all Listeria species. The N-terminus contains aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 60 publications
5
125
0
1
Order By: Relevance
“…The two dehydrogenases recognized by TcdA 26 -39 -specific antibodies, AdhE1 and LdhA, could also have potential roles in virulence. In Listeria monocytogenes, an aldehyde alcohol dehydrogenase is a housekeeping enzyme but is also a surface-exposed adhesin commonly referred to as LAP (Listeria adhesion protein) (33). In C. difficile, LdhA participates in a biosynthetic pathway, another member of which, HadA, has been found to be associated with biofilms, a key attribute linked to colonization (34).…”
Section: Discussionmentioning
confidence: 99%
“…The two dehydrogenases recognized by TcdA 26 -39 -specific antibodies, AdhE1 and LdhA, could also have potential roles in virulence. In Listeria monocytogenes, an aldehyde alcohol dehydrogenase is a housekeeping enzyme but is also a surface-exposed adhesin commonly referred to as LAP (Listeria adhesion protein) (33). In C. difficile, LdhA participates in a biosynthetic pathway, another member of which, HadA, has been found to be associated with biofilms, a key attribute linked to colonization (34).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of this alcohol acetaldehyde dehydrogenase with Hsp60, its host cell receptor, promotes bacterial adhesion to intestinal cells. [29][30][31][32] Anaerobic growth induces significant increases in the level of lap transcript and Lap secretion via the accessory secretion system SecA2 (see regulation section). Oral administration of lap-deficient strains to mice confirmed that Lap is essential for full virulence.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Our lab has identified Listeria adhesion protein (LAP), a 104-kDa alcohol acetaldehyde dehydrogenase (lmo1634), as a putative adhesion factor which promotes binding to cell lines of intestinal origin (29,31,32,46) and promotes translocation to the liver and spleen following oral infection of mice (6,31). LAP is present on the bacterial cell wall and is secreted by the SecA2 system (6).…”
mentioning
confidence: 99%